Literature Literature Review on the Effectiveness of the Merdeka Curriculum in Secondary Education in Indonesia Based on CIPP Evaluation - Fazar Nuriansyah; Eeng Ahman; Disman; Rasto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The Merdeka Curriculum was introduced to increase learning flexibility, encourage project-based learning, and integrate technology and local culture in the educational process. However, its implementation faces several challenges, including the varying readiness of educators, limited educational infrastructure, and disparities in access to technology and learning resources between regions, particularly in remote areas. This study aims to evaluate the effectiveness of the implementation of the Merdeka Curriculum in secondary schools using the CIPP (Context, Input, Process, Product) evaluation model. The study employs the Systematic Literature Review (SLR) method using the PRISMA framework to identify, screen, and analyze relevant studies. A total of 26 articles published between 2022 and 2024 were selected and analyzed to understand the effectiveness, opportunities, and challenges of curriculum implementation. The findings indicate that the Merdeka Curriculum provides greater flexibility in learning, promotes project-based learning, and supports the development of 21st century competencies such as critical thinking, creativity, collaboration, and digital literacy. In addition, the curriculum has a positive impact on increasing students’ learning motivation and encouraging more contextual learning practices. However, the effectiveness of its implementation is highly dependent on the readiness of teachers, the availability of learning infrastructure, and consistent policy support. To optimize the implementation of the Merdeka Curriculum, strengthening teacher capacity through continuous professional development, improving educational infrastructure, and refining project-based and authentic assessment systems are essential. Continuous evaluation and adaptive strategies are also needed to ensure that the curriculum remains relevant to global educational demands. The findings of this study provide insights for policymakers, educators, and researchers in improving the effectiveness of curriculum implementation and in designing more inclusive and sustainable educational policies in Indonesia